The Ban Formula: Non-Indian Authors and the Colonial State in the 1920s–30s. (June 2018) - Sethi, Devika
In a colonial context, and against the backdrop of an anti-colonial movement, it is all too easy to see censorship of publications operating along racial lines and to assume that only publications by Indian authors were subject to censorship. However, non-Indian authors—former colonial officials and soldiers, journalists and missionaries—writing in English on matters concerning India commanded audiences in their home countries in addition to being read by an influential section of the Indian population. Precisely because they escaped colonial stereotyping about 'seditious natives', non-Indian authors' words carried a greater illusion of neutrality and sometimes more weight. Their criticism of the colonial state or excessive approbation of nationalist leaders could less easily be dismissed as biased than that by Indians. By reconstructing the question of, and the controversy over, the possible banning of seven such books by the colonial state in the 1920s–30s, this article will question commonly held assumptions about the conduct of the censorship of publications in late colonial India.